Competitive Advantage to Mediate the Influence of Entrepreneurial Orientation, Product Innovation on SMEs Business Performance - Murniningsih, Rochiyati; Ghufron, Naufal; Fitriastuti, Triana (Jurnal Analisis Bisnis Ekonomi, 2023)
This research was conducted to examine and analyze the effect of entrepreneurial orientation, product innovation, on business performance through competitive advantage. The sample in this study was Micro, Small, and Medium Enterprises (SMEs) in Magelang Regency with a total of 306 respondents. The sampling method used was purposive sampling. The analytical tool in this study was multiple regression analysis with SPSS 25.0. The results of this study indicate that competitive advantage can mediate the effect of entrepreneurial orientation, product innovation on business performance and entrepreneurial orientation has a positive and significant effect on business performance, product innovation has a positive and significant effect on business performance, competitive advantage has a positive and significant effect on business performance, competitive advantage can mediate the effect of entrepreneurial orientation on business performance, competitive advantage can mediate the effect of product innovation on SMEs business performance.